Communication difficulties in adults with Intellectual Disability: Results from a national cross-sectional study - Smith, Martine; Mc Carron, Mary; Carroll, Rachael; Burke, Eilish; Manduchi, Beatrice; McCallion, Philip (My University, 2020)
Background: People with an intellectual disability (ID) are vulnerable to communication impairments, with consequences for employment, education, and social participation. Aims: To identify the communication skills of a population of adults (40+ years) with ID and explore relationships between individual and environmental factors and communication skills. Methods and procedures: Data from a sample of 601 adults with ID was selected from the Intellectual Disability Supplement to The Irish Longitudinal Study on Ageing (IDS-TILDA) addressing communication characteristics, demographics, co-morbidities, challenging behaviours, and social participation. A multiple regression model and a decision-making tree were built to identify factors related to communication abilities. Outcomes and results: Overall, 57.9 % of participants experienced communication difficulties, with 23.5 % reporting severe difficulties. Only 75.1 % of participants communicated verbally; more than half found communicating with professionals and non-familiar partners difficult. Level of ID, low social participation, challenging behaviours, and diagnosis of Down syndrome were significantly associated with communication difficulties. Conclusions and implications: Communication difficulties are prevalent in adults with ID and are influenced by complex factors. Interventions to enhance interaction and quality of life of individuals with ID should consider communication opportunities, needs, and barriers.
PUBLISHED
Keywords: Intellectual disability; Communication difficulties; Social participation; Regression model; Decision-making tree; Ageing; Inclusive Society; Aging and Intellectual Disability; Communication Impairment; Intellectual Disability; Communication